Conquering the host: Bordetella spp. and Pseudomonas aeruginosa molecular regulators in lung infection - Holban, Alina M.; Gregoire, Courtney M.; Gestal, Monica C. (Frontiers in Microbiology, 2022)
When bacteria sense cues from the host environment, stress responses are activated. Two component systems, sigma factors, small RNAs, ppGpp stringent response, and chaperones start coordinate the expression of virulence factors or immunomodulators to allow bacteria to respond. Although, some of these are well studied, such as the two-component systems, the contribution of other regulators, such as sigma factors or ppGpp, is increasingly gaining attention. Pseudomonas aeruginosa is the gold standard pathogen for studying the molecular mechanisms to sense and respond to environmental cues. Bordetella spp., on the other hand, is a microbial model for studying host-pathogen interactions at the molecular level. These two pathogens have the ability to colonize the lungs of patients with chronic diseases, suggesting that they have the potential to share a niche and interact. However, the molecular networks that facilitate adaptation of Bordetella spp. to cues are unclear. Here, we offer a side-by-side comparison of what is known about these diverse molecular mechanisms that bacteria utilize to counteract host immune responses, while highlighting the relatively unexplored interactions between them.